2013
DOI: 10.1089/acm.2011.0950
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biofield Treatment Dose and Distance in a Model of Cancer Cell Death

Abstract: Objective: This study assessed the potential influence of biofield treatment on cultured human cancer cells and whether such influence was affected by varying the duration of the treatment (dose) or the distance between the biofield practitioner and the target cells. Design: Biofield treatment dosage was assessed from a short distance (0.25 meters) in three independent experiments involving 1, 2, or 5 treatments, along with another set of three independent and comparable mock experiments. Biofield treatment di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 6 publications
(3 reference statements)
1
26
0
1
Order By: Relevance
“…Dabhade et al (2009) similarly show that measurable changes in particle size and hence surface area as well as crystallite size of antimony and bismuth metal powders resulted from the same external biofield treatment which they suggest may have caused a relatively high energy state to occur within the treated substances. Recently in Yount et al (2012) brain cancer treated in vitro from a controlled laboratory setting was shown to be positively inhibited in a biofield therapy dose response. With regard to plant life, Patil et al (2012) reported results from this energy of consciousness on micro-propagation response of Patchouli.…”
Section: Introductionmentioning
confidence: 99%
“…Dabhade et al (2009) similarly show that measurable changes in particle size and hence surface area as well as crystallite size of antimony and bismuth metal powders resulted from the same external biofield treatment which they suggest may have caused a relatively high energy state to occur within the treated substances. Recently in Yount et al (2012) brain cancer treated in vitro from a controlled laboratory setting was shown to be positively inhibited in a biofield therapy dose response. With regard to plant life, Patil et al (2012) reported results from this energy of consciousness on micro-propagation response of Patchouli.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are scientific evidence and large number of in vitro studies already reported for biofield treatment and its effect in cancer cells [26,27]. Previous studies indicated that biofield energy showed an inhibitory effect on metastasis and immune responses in cancer cell models [11,26,28].…”
Section: Resultsmentioning
confidence: 99%
“…However, there are scientific evidence and large number of in vitro studies already reported for biofield treatment and its effect in cancer cells [26,27]. Previous studies indicated that biofield energy showed an inhibitory effect on metastasis and immune responses in cancer cell models [11,26,28]. An exponential growth model was applied to the study data derived through time-lapse video microscopic technique which aims to take into account potential influence on cell death rates due to change the number of cells in each microscopic field throughout the observation period.…”
Section: Resultsmentioning
confidence: 99%
“…This process is known as "Biofield Energy Healing". Biofield Energy Healing has been approved as an alternative method that has an impact on various properties of living organisms in a costeffective manner [24,25]. The Trivedi Effect ® Unique Biofield Energy Healing Treatment has been known to alter the response in a wide-spectrum fields in living and nonliving systems viz.…”
Section: Shirley Theresa Holmlundn Et Al: Skin Nourishing Effects Ofmentioning
confidence: 99%